Novel route for rapid biosynthesis of copper nanoparticles using aqueous extract of Calotropis procera L. latex and their cytotoxicity on tumor cells - Harne, Shrikant; Sharma, Ashwinikumar; Dhaygude, Mayur; Joglekar, Shriram; Kodam, Kisan M.; Hudlikar, Manish (Colloids and Surfaces B-Biointerfaces, 2012)
This paper accounts for novel, low-cost, eco-friendly route for rapid biosynthesis of copper nanoparticles. Cysteine proteases present in the latex of Calotropis procera L. were used to fabricate copper nanoparticles from copper acetate. Copper nanoparticles were initially characterized by transmission electron microscopy (TEM) and X-ray diffraction technique (XRD). Transmission electron microscopy (TEM) was used to estimate the size and shape of nanoparticles. The average size of copper nanoparticles was found to be 15 +/- 1.7 nm. Energy dispersive analysis of X-rays (EDAX) showed distinct peaks of copper. Fourier transform infrared spectroscopy (FTIR) was performed to confirm capping behavior of the latex proteins that contributed to long term stability of copper nanoparticles (6 months) in aqueous medium. Copper nanoparticles synthesized by above method were monodisperse type. Cytotoxicity studies of latex stabilized copper nanoparticles were carried out on HeLa, A549 and BHK21 cell lines by MTT dye conversion assay. HeLa, A549 and BHK21 cells showed excellent viability even at 120 mu M concentration of copper nanoparticles. This shows that copper nanoparticles synthesized by above method hold excellent biocompatibility. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Biocompatible; Copper nanoparticles; FTIR; Latex; Tumor cells; X-ray diffraction technique (XRD)

Synthesis of copper nanoparticles in presence of surfactants and evaluation of heat transfer performance of copper nanofluid - Kapadnis, Chetan V.; Gundeli, Kartik P.; Saini, Daulat R.; Bhatkhande, Dhananjay S. (Journal of Nanofluids, 2017)
Copper nanoparticles were synthesized by reduction of copper nitrate hexahydrate using glucose as a green reducing agent. Effect of various synthesis parameters such as the amount of reducing agent, type of surfactant, the concentration of surfactant on particle size and morphology has been studied. Particles thus synthesized were characterized using analytical tools like X-ray Diffraction (XRD), Dynamic Light Scattering (DLS) and Scanning Electron Microscopy (SEM). XRD results show copper peaks at 2 angles 43.34, 50.48 and 74.19° corresponding to the planes (111), (200) and (220) respectively and possessing FCC (Face Centred Cubic) crystal lattice and polydispersed particles with crystallite size ranging from 43 to 103 nm. Further Cu nanoparticles were dispersed in water to prepare nanofluid and heat transfer properties such as heat transfer coefficient, viscosity and density were evaluated. Nanofluid models proposed elsewhere were also used for theoretical property evaluations. Nearly 100% increase in heat transfer coefficient was observed at 1% (by volume) particle concentration of copper nanoparticles in water.
Keywords: Chemical Reduction; Copper nanoparticles; green synthesis; Nanofluids; surfactant

Cu/Cu2O nanoparticles supported on a phenol-pyridyl COF as a heterogeneous catalyst for the synthesis of unsymmetrical diynes via glaser-hay coupling - Chakraborty, Debanjan; Nandi, Shyamapada; Mullangi, Dinesh; Haldar, Sattwick; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (ACS Applied Materials & Interfaces, 2019)
Covalent organic frameworks (COFs) are a new class of porous crystalline polymers with a modular construct that favors fiinctionalization. COF pores can be used to grow nanoparticles (nPs) with dramatic size reduction, stabilize them as dispersions, and provide excellent nP access. Embedding substrate binding sites in COFs can generate host-guest synergy, leading to enhanced catalytic activity. In this report, Cu/Cu2O nPs (2-3 nm) are grown on a COF, which is built by linking a phenolic trialdehyde and a triamine through Schiff bonds. Their micropores restrict the nP to exceptionally small sizes (similar to 2-3 nm), and the pore walls decorated with strategically positioned hydrogen-bonding phenolic groups anchor the substrates via hydrogen-bonding, whereas the basic pyridyl sites serve as cationic species to stabilize the [CuclusterCl2](2-) type reactive intermediates. This composite catalyst shows high activity for Glaser-Hay heterocoupling reactions, an essential 1,3-diyne yielding reaction with widespread applicability in organic synthesis and material science. Despite their broad successes in homocoupled products, preparation of unsymmetrical 1,3-diynes is challenging due to poor selectivity. Here, our COF-based Cu catalyst shows elevated selectivity toward heterocoupling product(s) (Cu nP loading 0.0992 mol %; turn over frequency: similar to 4S-50; turn over number: similar to 17S-190). The reversible redox activity at the Cu centers has been demonstrated by carrying out X-ray photoelectron spectroscopy on the frozen reactions, whereas the crucial interactions between the substrates and the binding sites in their optimized configurations have been modeled using density functional theory methods. This report emphasizes the utility of COFs in developing a heterogeneous catalyst for a truly challenging organic heterocoupling reaction.
Keywords: Copper nanoparticles; Covalent organic framework; Glaser-Hay heterocoupling; heterogeneous catalysis; unsymmetrical diynes